2015
DOI: 10.1101/gad.262170.115
|View full text |Cite
|
Sign up to set email alerts
|

Histone modifications predispose genome regions to breakage and translocation

Abstract: Chromosome translocations are well-established hallmarks of cancer cells and often occur at nonrandom sites in the genome. The molecular features that define recurrent chromosome breakpoints are largely unknown. Using a combination of bioinformatics, biochemical analysis, and cell-based assays, we identify here specific histone modifications as facilitators of chromosome breakage and translocations. We show enrichment of several histone modifications over clinically relevant translocation-prone genome regions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 41 publications
(41 reference statements)
0
35
1
Order By: Relevance
“…In leukemia, genomic breakpoints tend to be in introns and in genomic regions containing open chromatin [40]. Another study showed that open chromatin associated histone marks can facilitate DNA breakage and thus translocations [41]. These studies highlight the fact that rearrangements happen at nonrandom positions and that TAD rearrangements in cancer genome might occur at these specific locations.…”
Section: Tad Disruption and Cancermentioning
confidence: 99%
“…In leukemia, genomic breakpoints tend to be in introns and in genomic regions containing open chromatin [40]. Another study showed that open chromatin associated histone marks can facilitate DNA breakage and thus translocations [41]. These studies highlight the fact that rearrangements happen at nonrandom positions and that TAD rearrangements in cancer genome might occur at these specific locations.…”
Section: Tad Disruption and Cancermentioning
confidence: 99%
“…Further evidence for an aging-associated HSC epigenetic shift stems indirectly from comparative gene expression analyses, demonstrating deregulation of several components of chromatin organization and epigenetic maintenance genes in aged mouse HSCs, including genes of the PRC2 complex [58]. Finally, the Tom Misteli's laboratory has recently revealed that regions of high H3K4methylation in translocation prone regions of human HSCs facilitate chromosomal breakage and increased translocation frequency [59]. This suggests that epigenetic drift might also predispose aged HSCs to acquire distinct genomic translocations, a hypothesis that awaits experimental verification.…”
Section: Global Epigenetic Shifts and Changes In Polaritymentioning
confidence: 99%
“…During aging, there is a significant loss of histone methyltransferase SUV39H1 in HSCs leading to an overall decrease in H3K9me3 levels. H3K9me3 is a histone modification critical for heterochromatin maintenance and has been shown to protect DNA from double strand breaks (107). Thus, the age-associated decline of this histone methyltransferase could also contribute to the accrual of DNA damage due to genome instability (108).…”
Section: Drivers Of Dna Damagementioning
confidence: 99%